Analisis Sistem Antrian Jasa Pengujian di Laboratorium XYZ Dengan Menggunakan Software Arena - Fajrina R. Izzati; Hafid Syaifullah (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
The problem in the industrial sector that is often encountered is the problem of queuing. Queues occur when there is an imbalance between services and services offered, causing consumers to wait to get service. Laboratory queue simulation using Arena software. This research was carried out with the aim of analyzing the queuing conditions that occurred during the material A testing process at the XYZ Laboratory through simulation using Arena software. After carrying out a simulation with the Arena software, it was discovered that there were no queues for the material A testing queue activity at the XYZ Laboratory. From the results of the simulation data processing for material A testing queues in the XYZ laboratory, there are no queues and service times are optimal, so there is no need for corrective solutions. Based on the results of verification and validation, H0 is accepted because the value 0 is in the range μ1 – μ2 so it can be said to be valid. This states that the total time in the real situation (real system) is not significantly different from the output results in the Arena simulation that has been created.